2020
DOI: 10.1007/s12144-020-01080-w
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and sibling relationships: The mediating effect of social competence and behavior

Abstract: We investigated sibling relationships, temperament, and social competence and behavior of first-born and second-born children in China. A total of 212 Chinese children (M = 4.52, SD = .88) completed Sibling Relationships Scale, Temperament Scale, and Social Competence and Behavior Evaluation Scale. The results indicated that (1) for the first-born children, temperament subscales were positively related to their social competence and behavior, but had nothing to do with their sibling relationships, and children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Temperament affects a child's social development by determining how he perceives his nearby environment and how he reacts to the events (Rothbart & Bates, 2006;Qian, et al, 2020). Approach refers to how the child deals with new people and environments (Sanson et al, 2004), his sociability, and his adaptation to a different environment (Arabacıoğlu, 2019; Prior et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Temperament affects a child's social development by determining how he perceives his nearby environment and how he reacts to the events (Rothbart & Bates, 2006;Qian, et al, 2020). Approach refers to how the child deals with new people and environments (Sanson et al, 2004), his sociability, and his adaptation to a different environment (Arabacıoğlu, 2019; Prior et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, negative affect among infants and toddlers can predict their poor self-regulation ( Raikes et al, 2007 ; Putnam et al, 2008 ). Qian et al (2020) investigated two-child families and found that emotionality, activity, reactivity, social inhibition, and concentration among first-born children were significantly correlated with cooperation.…”
Section: Negative Affect and Social Skillsmentioning
confidence: 99%
“…rozwód rodziców starsze siostry są bardziej skłonne do udzielania wsparcia młodszemu rodzeństwu, -temperament. Znaczenie temperamentu oraz różnic w temperamencie rodzeństwa dla jakości ich relacji odnotowuje się głównie w badaniach dotyczących współpracy i konfliktów wśród sióstr i braci 69 . Na przykład w badaniu diad rodzeństwa, z których młodsze dzieci miały dwa lub trzy lata, nasilenie takich cech temperamentu, jak: nieadaptacyjność oraz negatywny nastrój współwystępowało z poziomem konfliktu, a dla jakości relacji między rodzeństwem cechy te miały większe znaczenie niż ich wiek i płeć 70 , -okres rozwojowy.…”
Section: Predyktory Jakości Relacji Między Rodzeństwemunclassified